Revealing the physics and evolution of galaxies and galaxy clusters with SKA continuum surveys - Prandoni, I.; Seymour, Nick (SPIE - Internatioal Society for Optocal Engineering, 2014)
In this chapter we provide an overview of the science enabled by radio continuum surveys in the SKA era, focusing on galaxy/galaxy cluster physics and evolution studies, and other relevant continuum science in the > 2020 scientific framework. We outline a number of reference radio-continuum surveys for SKA1 that can address such topics, and comprehensively discuss the most critical science requirements that we have identified. We highlight what should be achieved by SKA1, to guarantee a major leap forwards with respect to the pre-SKA era, considering the science advances expected in the coming years with existing and upcoming telescopes (JVLA, LOFAR, eMERLIN, and the three SKA precursors: MWA, ASKAP and MeerKAT). In this exercise we take in due account also the other waveband facilities coming online at the same time (e.g. Euclid, LSST, etc.), which tackle overlapping scientific goals, but in a different manner. In this respect particular attention has been payed to ensure that the proposed reference surveys are able to exploit the existing synergies with such facilities, so as to generate strong involvement from all astronomical communities, and leave a lasting legacy value. It is clear that a certain degree of freedom is allowed to some of the observational parameters. We believe it is very important to best fine-tune such parameters taking into proper account existing commensalities with SKA1 surveys addressing other science areas (HI galaxy science, magnetism, cosmology).